ANALYSIS OF STUDENTS' DIFFICULTIES FOR ENGLISH SUBJECT IN THE ISLAMIC EDUCATION DEPARTMENT AT STIT AQIDAH USYMUNI SUMENEP - Kamal, Moh. Zainol; Edyanto; Albadri (Fakultas Syariah dan Adab Universitas Nahdlatul Ulama Sunan Giri, 2025)
This study aims to identify the difficulties of PAI study program students in studying English courses. This study employed a qualitative approach with a descriptive method, aiming to describe and analyze in depth the difficulties faced by students in taking English courses. The sampling technique used was purposive sampling, which involves selecting informants based on specific criteria, such as semester level and English learning experience. Data collection was carried out through observation, semi-structured interviews, and documentation. It can be concluded that students of the Islamic Education Department Study Program at STIT Aqidah Usymuni Sumenep face various difficulties in taking English courses. These difficulties include aspects of basic language skills, namely listening, speaking, reading, and writing, with the main obstacles being limited vocabulary, lack of understanding of grammar, and low self-confidence in communicating orally. The factors causing these difficulties come from internal aspects such as low motivation, minimal background in previous English language learning, and learning anxiety, as well as from external factors such as less varied teaching methods, limited learning media, and lack of language practice environments.